EFEKTIVITAS LIDAH BUAYA (Aloe vera) DI DALAM MEREDUKSI FORMALIN PADA FILLET IKAN BANDENG (Chanos chanos Forsk) SELAMA PENYIMPANAN SUHU DINGIN - P, Annisa Fadhilah; Ma'ruf, Widodo Farid; Rianingsih, Laras (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Formalin is widespread used among the public, especially the fishermen and fish sellers. Saponin compound can reduce formaldehyde levels in fish flesh. Aloe vera contains high saponin compounds for approximately 5.651% per 100 grams. This research used Â milkfish fillet which are soaked in formalin solution and then soaked in the a solution of aloe vera added. The experimental design used was a completely randomized design (CRD) with 2x4 factorial. This experiment used two factors ((fish fillet soaked with aloe vera (L1) and fish fillet without soaked aloe vera (L0)) each factors consists of 4 levels of storage time (0, 3, 6, and 9 days) at chilled temperature. The parameter used are formaldehyde test, total colonies of bacteria, the moisture content, pH value, and organoleptic test. The result from experiment showed that the best concentration is 20% with the best soaking time is 60 minutes observed by the decreasing of formaldehyde content and organoleptic value. The result from main experiment showed that the different between treatment from aloe vera concentration and storage time gives significant effect (P<0,05) on organoleptic value, TPC, pH and moisture content. But, no interaction between two treatment (vera concentration and storage time) not there is significant effect on moisture content and pH value.Â